Long‐term ecological responses to landscape‐scale restoration in a western United States dry forest - Roccaforte, John P.; Huffman, David W.; Rodman, Kyle C.; Crouse, Joseph E.; Pedersen, Rory J.; Normandin, Donald P.; Fulé, Peter Z. (Restoration ecology, 2024)
Tree thinning and the application of prescribed surface fire are widespread forest restoration strategies used to regain ecological structure and function throughout dry forests of the western United States. Though such treatments are increasingly applied to broad extents, their effects on forest ecosystems are commonly evaluated at individual experimental sites or treatment units rather than large, operational landscapes. We evaluated the responses of forest structure, regeneration, old‐tree mortality, and tree growth to forest restoration for 21 years in a landscape‐scale (2114 ha) experiment in a Ponderosa pine (Pinus ponderosa)‐Gambel oak (Quercus gambelii) forest in northern Arizona, United States. Relative to the start of the experiment in 1996, tree density and basal area (BA) in the treated area were reduced by 56 and 38%, respectively, at the end of the study period compared to the untreated control. Conifer seedling densities generally declined and sprouting hardwoods increased following treatment. Mortality of old oak trees was significantly higher in the treated area compared to the control, likely due to fire‐caused injury during the prescribed burning. Mean annual BA increment of individual trees was 93% higher in the treated area than in the control. Our study provides new information on Ponderosa pine forest responses to restoration treatments at broad spatial scales and under realistic operational conditions. Results from this study can help inform landscape‐scale restoration projects in dry, fire‐dependent forests.